EFFORTS MADE BY THE GOVERNMENT TO RUN EDUCATION SMOOTHLY DURING THE CORONA EPIDEMIC: A STUDY - Kumari, Bhavna; Mishra, Laxmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this research paper, we will study the effects of the corona epidemic and know what effect it had on education in all the schools of the country. Its effect was that the education system in all the schools came to a halt. The government took immediate action to deal with all these things and various options were chosen to run education smoothly. All sections of the society were affected due to the corona epidemic, but the section that was most affected was the education world. Covid-19 (Corona virus) is a terrible infection, which spreads from people coming in contact with each other. This virus started from China in the year 2019. The first case of this infection was reported in China on 8 November. After this, this infection engulfed the whole world including China. The Covid-19 pandemic has greatly affected the world’s economy, educational system and social level. The study of the research paper has concluded that various efforts were made by the government to run education smoothly during Covid 19 and some challenges had to be faced.